The Effects of Return on Asset, Earning Per Share, And Price Earnings Ratio on Stock Return (Empirical Study on Transportation) - Kohar Mudzakar, Mochamad; Pramudya Wardanny, Intan; Ali, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The research objective was to determine the effect of return on asset, earnings per share, and price-earnings ratio on stock returns in transportation subsector companies listed on the Indonesia Stock Exchange. The exploration technique utilizes explanatory research. The population consists of financial reports from 12 companies. The sample selection technique uses a purposive sampling technique based on criteria that companies do not have negative ROA for the 2015-2018 period. This obtained a sample of 12 companies with a total of 48 data observations. Data analysis methods use panel data regression, processed with software E-Views 10. The results show that return on assets does not affect stock returns. Earnings per share, price earnings ratio affects stock returns. Simultaneously return on